(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Many sectors now embrace the concept of a digital environment where various kinds of sensors and local processors are linked to exchange information. These concepts have been used to build a variety of goods. The healthcare sector is one where many advancements are being made. The majority of illnesses may be prevented and treated with the help of medications. By taking the right medications, many dangerous and dangerous disorders may be healed. The suggested system includes an IoT-enabled medication reminder system that notifies patients when it is time to take their medications which makes the nursing practices to support healthcare needs quite easy and efficient. By giving audio-visual alert, it reminds the patient to take their medications at the appropriate time. The system aids in keeping track of the patient's medical information and medication administration.